Extracellular biosynthesis of CdTe quantum dots by the fungus fusarium oxysporum and their anti-bacterial activity - Syed, Asad; Ahmad, Absar (Spectrochimica Acta Part A-Molecular and Biomolecular Spectroscopy, 2013)
The growing demand for semiconductor [quantum dots (Q-dots)] nanoparticles has fuelled significant research in developing strategies for their synthesis and characterization. They are extensively investigated by the chemical route; on the other hand, use of microbial sources for biosynthesis witnessed the highly stable, water dispersible nanoparticles formation. Here we report, for the first time, an efficient fungal-mediated synthesis of highly fluorescent CdTe quantum dots at ambient conditions by the fungus Fusarium oxysporum when reacted with a mixture of CdCl2 and TeCl4. Characterization of these biosynthesized nanoparticles was carried out by different techniques such as Ultraviolet-visible (UV-Vis) spectroscopy, Photoluminescence (PL), X-ray Diffraction (XRD), X-ray Photoelectron spectroscopy (XPS), Transmission Electron Microscopy (TEM) and Fourier Transformed Infrared Spectroscopy (FTIR) analysis. CdTe nanoparticles shows antibacterial activity against Gram positive and Gram negative bacteria. The fungal based fabrication provides an economical, green chemistry approach for production of highly fluorescent CdTe quantum dots. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: antibacterial activity; Biosynthesis; CdTe; Fungus; Nanoparticles